2021
DOI: 10.1016/j.jsps.2021.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of colistin and fluoroquinolone in neonatal persistent late-onset sepsis

Abstract: Growing resistance of microorganisms to antibiotics for the treatment of late-onset sepsis (LOS) in premature infants has led physicians to use antibiotics that are not well studied in neonatal populations. We aimed to determine the efficacy and safety of colistin and fluoroquinolone for the treatment of persistent LOS. We retrospectively reviewed infants with gram-negative LOS, who received either colistin or fluoroquinolone therapy, to determine if there was a significant difference in kidney and liver funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It also needs to compare the general data of SG, MG, dead group and SG, detect the peripheral venous blood of SPI before treatment (BT) and after treatment (AT), use the automatic blood analyzer to observe and analyze the changes of PCT and RDW of 4 groups of SPI. [ 12 , 13 ]…”
Section: Objects and Methodsmentioning
confidence: 99%
“…It also needs to compare the general data of SG, MG, dead group and SG, detect the peripheral venous blood of SPI before treatment (BT) and after treatment (AT), use the automatic blood analyzer to observe and analyze the changes of PCT and RDW of 4 groups of SPI. [ 12 , 13 ]…”
Section: Objects and Methodsmentioning
confidence: 99%
“…The change between the beginning and end of treatment for creatinine and urea in both groups was insignificant; however, the change between the beginning and end of treatment for ALT and AST in the colistin group was statistically significant. 13 Zumrut, et al (2018) 15 showed 11 (10.5%) patients experienced nephrotoxicity. 63% of colistin-induced nephrotoxicity occurred during days 3-7.…”
Section: Patientsmentioning
confidence: 97%
“…Several studies have investigated the efficacy of colistin in neonates with multidrugresistant Gram-negative (MDR GN) sepsis (Table 1) [43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Efficacy In Neonatal Sepsismentioning
confidence: 99%